Pengaruh Persepsi Harga dan Physical Evidence pada Revisit Intention di Harris Resort Barelang Batam - Irawan, Resti; Wulandari, Dwi Pratiwi (Stupa, 2024)
This study was conducted due to problems related to Revisit Intention at Harris Resort Barelang Batam. Thus, the research purpose was to examine how guest satisfaction at Harris Resort Barelang Batam mediated the effects of price perception and tangible evidence on the intention to return. This kind of study employs the Causal Associative approach in quantitative descriptive research. The research participants were visitors who had stayed at Harris Resort Barelang Batam; a non-probability sampling procedure was used to select 150 respondents for the sample. Questionnaires with a Likert scale that have been verified for validity and reliability are used in data-gathering procedures. A tabular presentation of the analysis's findings is provided for the data from this study, which were processed using SMART-PLS 3.0. The study's findings demonstrated that Price Perception (X1), Physical Evidence (X2), Revisiting Intention (Y), and Guest Satisfaction (M) were all in the good category, scoring 3.79%, 3.87%, 3.78%, and 3.73% respectively. Based on the hypothesis testing using Bootstrapping on SmartPLS with sig1.96, < 0,05 atau t-value > there is a positive and significant impact from the variables Price Perception and Physical Evidence on Revisiting Intention and there is a positive and significant impact from the Guest Satisfaction variable mediating Price Perception and Physical Evidence on Revisiting Intention.